Intracranial dural arteriovenous fistula successfully treated by combined open–endovascular procedure. Issue 6 (22nd February 2010) - Hallaert, Giorgio G; De Keukeleire, Katrien M; Vanhauwaert, Dimitri J; Defreyne, Luc; Van Roost, Dirk
Abstract : Intracranial dural arteriovenous fistulas constitute a rare though potentially devastating disease. Because the arterial (high-pressure) blood flow drains directly into the low-pressure venous system, there is a high risk of bleeding and associated neurological deficit. The classifications by Borden and Cognard underline the correlation between bleeding risk and venous drainage pattern of the fistula. There are different treatment options for this vascular pathology, which always poses a challenge for the physicians involved to offer the optimal treatment for an individual patient. This case report illustrates how combining forces between the neurosurgical and endovascular team benefits outcome. Simultaneously, this contributes to the growing amount of evidence that a new endovascular technique with transarterial ONYX embolisation enables complete obliteration of the vascular malformation.